Phosphorylated-Survivin at Ser81 Induced Protein Kinase A (PKA): A Back Loop - Ferry Sandra; Roya Khosravi-Far (The Indonesian Biomedical Journal, 2011)
BACKGROUND: Survivin, a bifunctional protein, acts as suppressor of apoptosis and has an essential role in mitosis. Survivin is physically phosphorylated on Thr34, and other important sites such as Thr117, Ser20, Thr48 and Ser81. Our previous report has shown that Ser81 of survivin plays role in cytoprotection. In order to investigate the underlying mechanism, all motifs with medium stringency were scanned. We found that site of survivin at Ser81 was correlated to PKA, which is well reported to many cell signal machineries, including cell survival. Therefore, we focused our current investigation in finding possible correlation and interaction between survivin’s Ser81 site and PKA.METHODS: Wild-type survivin (Survivin), antisense survivin (Survivin-AS), mutated-survivin and mutated-survivin Ser81Ala (Survivin-S81A) were constructed. Each retroviral product was produced. Some cell lysates were prepared and immunoprecipitated. For analysis, we performed immunoblotting and PKA’s activity assays.RESULTS: In our current results, phosphorylated-PKA was correlated with survivin. Infection of survivin could lead to acceleration of PKA’s activity in a viral particle dependent manner. This positive back loop induction by survivin was shown to be correlated to Ser81 site, since survivin-mediated PKA activity was not resulted by mutated form of survivin at Ser81 to nonphosphorylatable Ala (S81A).CONCLUSIONS: Our results suggested a possible back loop of survivin to activate PKA, and Ser81 could be an important site to mediate the survivin-PKA back loop signaling. Survivin-induced activation of PKA might be related to cytoprotection.KEYWORDS: survivin, S81A, L929, PKA